142k views
5 votes
4×9×8^-1×3^-3/6^-1 .Ans is 1 but I want the method.​

4×9×8^-1×3^-3/6^-1 .Ans is 1 but I want the method.​-example-1
User LTJ
by
5.7k points

2 Answers

2 votes

Answer:

Hi, Hope this will help :-)

4×9×8^-1×3^-3/6^-1 .Ans is 1 but I want the method.​-example-1
User Joel Van Hollebeke
by
4.7k points
3 votes
  • Answer:

1

  • Explanation:

(4×9×8⁻¹×3⁻³)/6⁻¹ =

= (2²×3²×2⁻³×3⁻³)/2⁻¹×3⁻¹

= (2²×2⁻³×3²×3⁻³)/2⁻¹×3⁻¹

= 2⁻¹×3⁻¹/2⁻¹×3⁻¹

= 1

User Leinir
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.